Recent Advances in Lithium–Carbon Dioxide Batteries. Issue 2 (11th September 2020) - Yu, Xingwen; Manthiram, Arumugam
Abstract : Toward global sustainable development, lithium–carbon dioxide (Li–CO2 ) batteries not only serve as an energy‐storage technology but also represent a CO2 capture system. Since the beginning of their research in this decade, Li–CO2 batteries have attracted growing attention. However, Li–CO2 batteries are still in their infancy and are facing many scientific and technological challenges. From a fundamental perspective, the reaction mechanism of CO2 cathode is not yet clear enough. Technologically, the high overpotential, low power density, poor rate capability, and limited cycle life impede the development of Li–CO2 batteries for practical applications. Herein, the recent research progress in Li–CO2 batteries in terms of reaction mechanisms, cathode catalyst design, electrolyte management, and anode protection are first summarized. In light of the state‐of‐the‐art research advances, future perspectives and research directions are then put forward, aiming to provide insightful information for the development of practical Li–CO2 batteries. Abstract : Recent research progress in Li–CO2 batteries has been reviewed in terms of reaction mechanisms, electrochemical performance, catalyst design, electrolyte exploration, and lithium‐anode protection. The major challenges of cell components, especially the cathode catalysts, are identified and analyzed. Perspectives on future research directions are highlighted to inspire the research community and spur the practical development of Li–CO2 battery technology.